Application of early warning system (EWS) in patients with cardiovascular disorders : a descriptive study - Bobonera, Teguh Theryana; Mubin, Mohammad Fatkhul; Pohan, Vivi Yosafianti; Soesanto, Edy; Astuti, Rahayu (Universitas Muhammadiyah Semarang, 2024)
Incidents of clients experiencing sudden cardiac arrest in the inpatient setting or unexpected and unavoidable deaths in the inpatient setting are common. One of the efforts to improve quality related to patient safety in hospitals is the application of the Early Warning System (EWS) to clinical changes in patients in hospital inpatient installations. The purpose of this study was to describe the application of EWS in clients with cardiovascular system disorders, including the risk of seriousness, respiratory rate, oxygen saturation, use of oxygen supplements, systolic blood pressure, pulse frequency, level of consciousness, and body temperature. This study is an observational descriptive study with a cross-sectional approach. The number of respondents was 48 people, namely clients who were treated with diseases of the cardiovascular system. Data analysis using descriptive analysis. The characteristics of respondents obtained in this study showed that the majority of respondents were female (54.2%), the majority of medical diagnoses were congestive heart failure, which was 43.75%, and the average length of stay was 4.63 days. Most of the patient's risk of seriousness was in the moderate category, namely 22 respondents (45.8%). Assessment of clients with cardiovascular system disorders with EWS in this study can predict the level of patient care so that preventive measures can be taken. Recommendations for future research are research on predicting patient mortality using EWS.